Splenic artery aneurysm rupture in pregnancy: challenges in diagnosis and the importance of multidisciplinary management. Issue 4 (20th April 2022) - Vaughan, Emily; Carlsson, Tarryn; Brooks, Marcus; Elhodaiby, Mohamed
Abstract : This case of acute rupture of a splenic artery aneurysm in a patient 35 weeks pregnant demonstrates the difficulties in diagnosis and importance of multidisciplinary team management for surgical emergencies in pregnancy. A women in her early 30s presented at 35 weeks pregnant with sudden onset of severe epigastric pain and shortness of breath and was found to be tachycardic with a raised lactate. Differentials included a possible vascular event or pulmonary embolism. A CT scan demonstrated free fluid and likely ruptured splenic artery aneurysm. A rapid, thorough preoperative meeting enabled us to integrate multidisciplinary care effectively. She underwent coiling of her splenic artery, which was essential to reduce further intraoperative blood loss, followed by a midline incision for caesarean section of her baby and splenectomy. She had a long stay in the intensive care unit (ITU) and complex postoperative course but was discharged after 2 months to be reunited with her baby who was in good condition.